Pengaruh Indeks Pembangunan Manusia, Tenaga Kerja, Pengangguran dan Kemiskinan Terhadap Pertumbuhan Ekonomi di Indonesia - Sari, Novi Lusita (Universitas Negeri Surabaya, 2023)
Poverty is a development problem that must be minimized because it can cause various social problems. Based on existing theories and several studies that have been conducted, the problem of poverty is generally related to several factors such as the quality of human resources, unemployment and economic growth. This study aims to determine the effect of the human development index (HDI), the unemployment rate, and economic growth directly on the poverty rate. Furthermore, it will also be seen the indirect effect of HDI and economic growth through unemployment in influencing poverty levels. The basic method in this research is descriptive. The data analysis technique used is descriptive statistics. The data used is secondary data in the form of panel data from all provinces in Indonesia. The results of this study indicate that the human development index (HDI) indirectly through the outpouring of unemployment has a significant and negative effect on the population, economic growth indirectly, through unemployment does not affect the number of poor people in Indonesia.